DASAR MEMILIH METODE PENDIDIKAN DALAM PERSPEKTIF AL QURAN DAN HADIS - Juliwansyah, Juliwansyah; AM, Rusydi; Charles, Charles (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2022)
This study aims to examine a teacher must have the basic considerations before using a method. The basic considerations for choosing a method in learning are an important part of the learning strategy, because it functions as a basis for presenting, describing, giving examples, and giving training to students to achieve certain goals. So it can be concluded that, there are at least five forms of learning methods taught by the Qur'an. These methods include; Story or lecture method. This method is in line with the Qur'an sura al-Kahf verses 66-67. Methods of discussion, question and answer and dialogue. This method is in line with the Qur'an sura al-Anbiya verses 52-61. The awareness method, this method is in line with Al-Qur'an letter Luqman verse 13. The method of giving punishment. This method is in line with the Qur'an letter al-Nisa verse 34. Furthermore, the last method is the exemplary method. This method is in line with the Qur'an al-Ahzab verse 21